Minimum wages and mental health: Evidence from Canada - Yihong Bai; Michael R. Veall (Elsevier, 2023)
International evidence on the effect of minimum wages on mental health has been mixed. Estimation has used different types of variation in the minimum wage. In some countries such as the UK, the minimum wage is set nationally. In the United States, it is largely set subnationally. The resulting across state and time variation has recently been used to estimate that minimum wage increases have a positive effect on mental health. We exploit similar and substantial subnational level variation for Canada, using a longitudinal health survey panel available from 1994 to 2011. Using difference-in-difference and triple difference methods with individual fixed effects, we find that minimum wage increases are associated with modest reductions in distress and depression symptoms, largely for males.